2001
DOI: 10.1177/0011000001295004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Eating Disorders in Women

Abstract: This article reviews the most recent treatment literature for anorexia nervosa, bulimia nervosa, and binge eating disorder and serves as a guide for recommended readings and therapist resources. The primary focus is on empirically tested treatment modalities; for each of these approaches reviewed, the theoretical background, nature of the intervention, and existing empirical support are summarized. The article also presents less researched, albeit promising, approaches to eating disorder treatment, describing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 107 publications
0
30
0
Order By: Relevance
“…This was not always successful, but it appeared crucial to the cases that did go well. Although family visits are often included in intensive outpatient and inpatient programs (Costin, 1999), and others have suggested that family therapy is suited to clients from collectivistic cultures (Stein et al, 2001;Ting & Hwang, 2007), the present study is the only one we know of that describes Asian parents' involvement in treating EDs. Perhaps the most important clinical skill here was flexibility and openness to, for example, seeking out the one parent who was more accessible, or permitting unorthodox arrangements such as a mother sitting in on sessions, even as issues of autonomy were being addressed.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…This was not always successful, but it appeared crucial to the cases that did go well. Although family visits are often included in intensive outpatient and inpatient programs (Costin, 1999), and others have suggested that family therapy is suited to clients from collectivistic cultures (Stein et al, 2001;Ting & Hwang, 2007), the present study is the only one we know of that describes Asian parents' involvement in treating EDs. Perhaps the most important clinical skill here was flexibility and openness to, for example, seeking out the one parent who was more accessible, or permitting unorthodox arrangements such as a mother sitting in on sessions, even as issues of autonomy were being addressed.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Within the eating disorder field, many recovered patients subsequently resume their binge and/or purge behaviors and individuals with AN often do not complete treatment, dropping out prematurely 37,75,103. Family-based behavioral treatment for obesity has been shown to be successful in the short-term 87, but the targeted healthy behaviors are difficult to sustain over time.…”
Section: From a Clinical Perspective: Extending Beyond The Individualmentioning
confidence: 99%
“…The research on the treatment of eating disorders for women of color is limited (Stein, Saelens, Dounchis, Lewczyk, Swenson, & Wilfley, 2001). The following will address general treatment considerations and then provide perspectives on multiculturally-informed feminist approaches to the treatment of body image and eating disorder issues for Asian American women.…”
Section: Treatment Considerationsmentioning
confidence: 99%